Palynological Zonations and Sequence Stratigraphic Analysis of Sediments in Benin West-1, Anambra Basin, Nigeria (Journal of Scientific Research, 2016)
Palynoflora analyses from Benin west -1, Anambra Basin has unfold three palynozones based on abundance, composition of palynoflora and cluster analysis. Palynozone-1 has been dated as Late Maastrichtian age and belong to the lowermost Imo Shale, palynozone-2; Middle Eocene and palynozone -3  is  dated Lutetian to Bartonian age. Sediments between   depth intervals of 2649-2560 m is marked a sequence boundary, 1650-2560 m, and 970-1190 m is delineated as high stand system tract. Shaly intervals from the depth of 1644 m, and 1234 m recorded  acme of palynoflora (Zonocostites ramonae, Monoporites annulatus, Verrucatosporites spinosus, Botryococcus braunii) and probably fingerprints a condensed section. The condensed section intervals (1644 m and 1234 m) may depict   good source rock and exploration targets.